A Histological and Histochemical Study on Olfactory Bulbs to Detection Amyloid Protein Depositions by Congo-Red and Routine Staining Techniques - Rajaa Ali Moheiseen Al- Taee1 , Muna Hussain Al-Aameli2 , Yarub Modhar Al-Qazwini3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study, histological and histochemical techniques were used to examine olfactory bulbs in the albinorat male. Thirty male albino rats were split into three age groups (10 animals each) in the current research:Group I: consider as a control group, including adult animals aged 3 months .Group II: include animalsaged 6 months. Group III: include animals aged 12 months. The histological architecture of the layersof olfactory bulbs and their main cells was identified by using H & E staining techniques, meanwhile thecomposition of each layer in albino rat was evident. In the glomerular and mitral cell layer of group III,olfactory bulbs showed reduced neural density. Modified staining with Congo - red was conducted forhistochemical studies. Compacted amyloid cores were found in group III animals’ olfactory bulbs, whiledispersed amyloid cores were found in group II&III olfactory bulbs’ cortex. The present study adds to ourknowledge of the impact of amyloid protein on olfactory bulbs and their prospective neurodegenerationinvolvement.